Características físicas, químicas e biomecânicas dos ossos de ratas ovariectomizadas tratadas com fluoreto de sódio - Mello, Luiz Carlos de Paula (2003)
Ovariectomized (ovx) rat bones were used to evaluate the effects of sodium fluoride treatment on bone physical, chemical and biomechanical parameters. Wistar rats, with four months of age, were randomly divided in: basal, intact and ovx treated with sodium fluoride (0, 20, 40, 60, 80 and 100 ppm) groups. The basal group was sacrificed in the beginning of the experiment and the other groups after 2, 4, 6 and 8 months of treatment. Bone demineralization of femur due to osteopenia (induced by sexual steroids deficiency) resulted in lower values of bone density that resulted in lower values of biomechanical parameters when compared to intact group. Higher values of maximum force, failure force, resilience and stiffness of femur from ovx group treated with sodium fluoride, when compared to ovx group, were observed. The use of sodium fluoride as a therapeutic agent inhibited the osteopenia induced by castration and enhanced the bone quality, mainly when low dose was used (40 ppm)during short periods of treatment (2 and 4 months).